Music as a complementary therapy in medical treatment (Medical Journal of Indonesia, 2002)
Music can act not only as a source of enjoyable sound that gives pleasant feeling, but also a source of healing. Music as a therapy has developed, supported by many researches conducted by experts in music, education and medicine. The impact of music therapy can be observed in many case studies, showing the positive effects of music to the betterment of humanâs neuro-behavior, emotional and physical states. Some reasons to use music as a therapy are: toget audioanalgesic response, to focus attention, to reinforce learning, to enhance interpersonal relationships, and to promote mind-body health in the medical staff. The use of music to help patients with non-infectious diseases such as Alzheimer disease, autism, cancer, headache, heart disease and stroke are described along with experiments and case studies on these diseases. However controversies around music therapy occurred. Therefore, more experiments need to be taken in order to clear the controversies and to use music as a therapy in the present and future medical treatment. (Med J Indones 2002; 11: 250-7).Keywords: therapeutic effect, music therapy, Alzheimer, autism, cancer, stroke